USP20 is a predictor of poor prognosis in colorectal cancer and associated with lymph node metastasis, immune infiltration and chemotherapy resistance - Jin, RuiRi; Luo, ZhiPeng; Jun-Li,; Tao, Qing; Wang, Peng; Cai, XueSheng; Jiang, LongZhou; Zeng, ChunYan; Chen, YouXiang (Frontiers in Oncology, 2023)
Background: Colorectal cancer (CRC) is a highly prevalent malignancy with a poor prognosis. USP20 is considered to play an important role in tumor progression. However, the role of USP20 in CRC remains unclear. Methods: Application of bioinformatics to analyze the expression and prognosis of USP20 in pan-cancer and then to explore the relationship between USP20 expression and immune infiltration, immune checkpoints, chemotherapy resistance in CRC. The differential expression and prognostic role of USP20 in CRC was validated by PCR and immunohistochemistry. COX univariate and multivariate analyses were performed to assess risk factors for poor prognosis of CRC, and new prognostic prediction models were constructed and evaluated by ROC and DCA. Overexpression of USP20 on cells to explore the effect of USP20 on the functionalities of CRC cells. Enrichment analysis were used to explore the possible mechanism of USP20 in CRC. Results: The expression of USP20 is lower in CRC tissues than adjacent normal tissues. CRC patients with high USP20 expression level had shorter OS compared with low USP20 expression patients. Correlation analysis showed that USP20 expression was associated with lymph node metastasis. COX regression analysis revealed USP20 as an independent risk factor for poor prognosis in CRC patients. ROC and DCA analyses showed that the performance of newly constructed prediction model in this study was better than the traditional TNM model. Immune infiltration analysis shown that the USP20 expression is closely associated with T cell infiltration in CRC. A Co-expression analysis shown that USP20 expression was positively correlated with several immune checkpoint genes including ADORA2A, CD160, CD27 and TNFRSF25 and positive association with multiple multi-drug resistance genes such as MRP1, MRP3，MRP5. USP20 expression positively correlates with multiple anticancer drugs IC50. Cellular functionalities showed that overexpression of USP20 enhanced the migration and invasive ability of CRC cells. The enrichment pathway analyses showed the USP20 may play a role by NOTCH pathway, HEDGEHOG pathway and BETA CATENIN pathway. Conclusion: USP20 is a differentially expressed gene associated with prognosis in CRC. USP20 enhances CRC cells metastasis and is associated with immune infiltration, immune checkpoints, and chemotherapy resistance.